(untitled) (Mother Language, 2026)
Among the Garo ethnic groups, the youngest daughter inherit property and land from their mother. In the traditional Garo society, men do not inherit any property. However, as per the mother’s clan, the mother has the right over the children, and receive the name of her clan or Mahari. Property ownership helps a woman to understand and pursue all phenomena related to the power and authority vested, and strives to express the mentality. She tries to express it through her physical expression, behavioral expression, and use of language, choice of words, authoritative behavior, and commanding voices. This research has used the phenomenology based ethnography method to collect qualitative data. The purpose of conducting the study is to determine the compatibility between her land ownership and raising voices in regards to her personal interest, family interest as well as social interest, to understand the freedom of speech of women as well as men in Garo society. Mother Language, 2025; 9 (2): 5-20